Physical Activity and Systemic Lupus Erythematosus Among European Populations: A Two-Sample Mendelian Randomization Study - Huang, Shuo; Tian, Fengyuan; Yang, Xiaoxuan; Fang, Sijia; Fan, Yongsheng; Bao, Jie (Frontiers in Genetics, 2022)
Background: The causal relationship between physical activity (PA) and systemic lupus erythematosus (SLE) remains uncertain. We aimed to assess the causal effect of PA on SLE by two-sample Mendelian randomization (MR) study. Methods: Summary statistics of SLE were obtained from a genome-wide association study (GWAS) meta-analysis of European descent, including 4,036 cases and 6,959 controls. Genetic instruments for PA, including MVPA, VPA, SSOE, and average acceleration, were identified from a large-scale GWAS meta-analysis among 377,234 individuals of European ancestry from United Kingdom biobank and Atherosclerosis Risk in Communities (ARIC) study, and another GWAS with 91,105 European participants was employed for sedentary behavior. The two-sample MR study was conducted to estimate causal relationship between PA and SLE, with the inverse-variance weighted (IVW) method, simple- and weighted-median method. Moreover, MR-Egger regression, MR-PRESSO and leave-one-out analysis were performed to evaluate the potential pleiotropy effect. Results: In the end, we totally selected 37 SNPs (15 SNPs for MVPA, 5 SNPs for VPA, 9 SNPs for SSOE, 5 SNPs for average acceleration and 3 SNPs for sedentary behavior). According to the IVW results, as the primary method, we found that genetically predicted PA was not causally associated with risk of SLE (MVPA: OR 0.44, 95% CI 0.09–2.10, p = 0.305; VPA: OR 0.20, 95% CI 0.00–18.97, p = 0.490; SSOE: OR 0.96, 95% CI 0.03–29.24, p = 0.983; average acceleration: OR 0.91, 95% CI 0.79–1.05, p = 0.190; sedentary behavior: OR 1.54, 95% CI 0.35–6.81, p = 0.572). MR-Egger, MR-PRESSO, and leave-one-out analysis did not indicate horizontal pleiotropy. Conclusions: Our MR study suggested that genetically predicted PA was not causally associated with SLE among the European populations.